The effect of Er,Cr:YSGG laser irradiation on the apical leakage of retrograde cavity - Asnaashari, Mohammad; Fekrazad, Reza; Dehghan Menshadi, Fatemeh; Seifi, Masoud (Iranian Endodontic Journal, 2010)
INTRODUCTION: Controversial results have been reported when organic acids, ultrasonic instruments and laser techniques were used to remove smear layer in endodontic treatments. The aim of this study was to evaluate the effect of removing debris and smear layer by Er,Cr:YSGG laser irradiation on the apical leakage of retrograde cavities. MATERIALS AND METHODS: In this ex vivo study, 24 extracted mandibular single-rooted teeth were selected and instrumented up to K-file size #35. Approximately 3 mm of root apices were dissected perpendicular to the root’s long axis. Retrograde cavities with 3 mm depth were prepared and the teeth were randomly assigned to two groups. In one group, the retrograde cavities were filled with amalgam and in the other group, the dentinal surface of the retrograde cavities were lased with Er,Cr:YSGG laser (2W, 15 seconds, G4 tip). The cavities were filled with amalgam; all tooth surfaces except for dissected outsides were covered with blue wax. Then the teeth were immersed in 2% methylene blue dye for 48 hours. The amount of dye penetration into sagittal sections was measured by stereomicroscope at ×20 magnification by two independent observers who were blinded to the experiment. Data were statistically analyzed using student t-test. RESULTS: This study demonstrated that dye penetration was 0.8 mm (±0.53) in the lased and 0.97 mm (±0.54) in the non-lased group. It showed that, Er,Cr:YSGG laser can remove the debris and smear layer and consequently reduces the amount of dye penetration, although, the difference between the two groups was not statistically significant. CONCLUSION: This study showed that dye penetration was less in lased group because of the better seal of the dissected surface due to the better removal of the debris and smear layer by laser; further investigations are recommended in this field. [Iranian Endodontic Journal 2009;4(4):144-8]